Morocco : Financial System Stability Assessment; Update. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This paper presents an update to the Financial System Stability Assessment on Morocco. Major reforms have been achieved since the 2002 Financial Sector Assessment Program (FSAP) within a policy of actively promoting economic and financial sector opening. The 2002 FSAP recommendations have been largely implemented. Although the financial system is stable and considerably more robust than in the past, the liberalization of capital flows and increased exchange rate flexibility present challenges for the monetary authorities, financial regulators, financial institutions, and markets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet